What do you say and how do you say it: Information disclosure in Latin American firms (2016)
Firms in Latin America could differentiate themselves by adopting better information disclosure practices. In this paper, we construct an Information Disclosure Index (IDI) for a sample of 454 firms in the six largest Latin America countries. We look at 3.191 company reports and show that firms with better disclosure practices have better market valuation (Tobin’s Q) and operating performance (ROE). We then measure the tone of the information disclosed using word content analysis, and find that uncertainty in tone is negatively associated with higher firm valuation (Tobin’s Q) and better financial performance (ROE).